Needs assessment Report: Development of Grazing & Feeding Advisory System; Water-availability prediction tools; Water Management Strategy Guide - Muñoz, Ángel G.; Demissie, Teferi (International Livestock Research Institute, 2026)
Pastoral and agropastoral livestock systems are central to livelihoods across East Africa, providing milk and meat, generating cash income, serving as a store of wealth and social insurance, and underpinning local cultural and economic systems. Household food security and livelihood resilience in these systems depend critically on herd condition, which in turn is driven by seasonal forage and water availability. As a result, timely and reliable seasonal grazing and feeding forecasts, when combined with operational feed budgeting and stocking rate advisory tools, can substantially reduce risk, improve preparedness, and strengthen resilience to climate variability and shocks (e.g., McGahey et al., 2014). However, feed availability in pastoral landscapes is highly variable both spatially and temporally. It is influenced not only by total seasonal rainfall, but also by rainfall timing, intra-seasonal dry spells, inter-annual droughts, and local biophysical factors such as soil types and rangeland condition. This variability creates a strong need for proactive management of stocking rates, mobility, feed supplementation, and targeted interventions. Without advance information, households are often forced into reactive coping strategies that lead to herd losses and long-term degradation of their livelihoods. Emerging operational tools and services, such as AgriWebb, Foragecaster/Pasture.io, and FoodAgility’s Foragecaster project, demonstrate how climate and Earth-observation data can be translated into decision-ready information on forage availability and carrying capacity, highlighting the growing demand for scalable, locally relevant livestock advisory products. The scientific and operational literatures converge on three core needs for effective livestock early warning and decision support systems. First, there is a need for robust seasonal-to-multi-seasonal forecasts of precipitation and derived forage conditions that are skillful at relevant spatial scales. Second, locally calibrated transfer functions are required to translate precipitation and vegetation signals into actionable indicators such as biomass availability, carrying capacity and feed budgets. These relationships must reflect local rangeland types, management practices, and livestock systems. Third, advisory services must be explicitly uncertainty-aware, translating probabilistic forecasts into clear thresholds, risk categories, and staged response options that support anticipatory decision-making rather than reactive crisis response. Addressing these needs through integrated livestock advisory services enables pastoralists, extension agents, and humanitarian and development actors to take earlier action, thereby reducing economic losses, mitigating the humanitarian impacts of drought, and strengthening long-term pastoral resilience. This need assessment underscores the importance of investing in climate-informed, operational livestock advisory systems that bridge science, local knowledge, and decision-making at scale (FEWS NET; Funk et al.; IUCN/ILRI).